The Gold Market and the Value of the U.S. Dollar - Abdullah, Adam; Abu Bakar, Mohd Jaffri (Canadian Center of Science and Education, 2015)
The aim of this research is to determine to what extent the price of gold is suppressed, thereby revealing an internal structural problem within the global monetary system. Historical manipulation could only have been done by controlling the value of money under a fractional reserve gold standard through the physical demand for, and supply of gold, in relation to official reserves held at a central bank. More recently, the price of gold is largely influenced through paper trades, as a function of the operation of the gold market involving gold derivatives, in conjunction with physical trades and changes in official reserves. This research adopts a qualitative interpretation and numerical analysis to analyze the extent of market concentration and price manipulation. Our findings reveal that the gold market is largely deterministic rather than stochastic in nature. It also reveals that markets are not only subject to a fractional reserve banking system, but also a fractional reserve gold market, highlighting systemic instability inherent within the modern monetary system, and especially the value of the U.S. dollar and related dollar denominated assets.